About necessity of new speciality introduction for pharmacists - V. A. Kutyakov; L. V. Trufanova; A. B. Salmina (Бюллетень сибирской медицины)
In connection with changes in the pharmaceutical market and in public health services sphere necessity of a new speciality introduction for the pharmacists conducting judicial-chemical (chemical-toxicological) researches in establishments of public health services is proved. The speciality statement «Analytical toxicology» completely corresponds to positions of the Bolonsky Convention of 2003 and prospects of development of pharmaceutical industry.